Development of Environmental Action Plans for Adaptation to Climate Change: A Perspective of Air Quality Management - Han-Shi Chen; Kei-Iong Tam; Yu-Lin Zhao; Lan Yuan; Weiyi Wang; Merrisa Lin; Pen-Chi Chiang (Aerosol and Air Quality Research)
Abstract The impacts of climate change on air quality (tropospheric ozone pollution, particulate matter pollution, atmospheric deposition effect, and extreme weather events) greatly threaten most creatures on the earth who need to breathe fresh and non-toxic air. To respond to the impacts of climate change concerning air, many countries have proposed corresponding adaptation plans to reduce these impacts. In this study, a Climate Change Adaptation Plan concerning Air (CCAP-Air) is proposed based on the summary of policies and strategies in developed countries (United States, United Kingdom, Germany, Japan, and Australia), where five main strategies were suggested, including integrating the impacts of climate change on air quality into legislation, developing models to simulate the impacts of climate change on air quality, incorporating nature-based solutions into air quality management, considering AIoT (Artificial Intelligence Internet of Things) into climate change monitoring and governance, and establishing green finance system for tackling climate change. The CCAP-Air proposed in the current work provides insights for countries and regions to solve climate change challenges with respect to air quality management.